Mare's folliculogenesis: Assessment of ovarian and perifollicular vascular perfusion by doppler ultrasound - Uliani, Renata Cristina [UNESP]; Silva, Luciano Andrade; Alvarenga, Marco Antonio [UNESP] (My University, 2011)
Background: Ultrasound Doppler is a new technology that has recently been used in large animal reproduction. As the conventional ultrasound (B-mode) it is a noninvasive technique, but with the advantage of allows the assessment of the hemodynamic of reproductive tract in real time. The observation of important features of the vascularization and changes that occur during physiological processes that were not previously seen on B-mode encourage a reassessment of the concepts already established on the events of the reproductive physiology of animals and their applications. Review: In attempt to re-understand the equine reproductive physiology and finding practical uses to this new technique, authors showed that, during the follicular deviation, features are observed by Doppler before being observed under B-mode ultrasound like changes in the speed of the blood flow two days before deviation of the follicle size and one day before the increase in blood flow area of the follicular wall. According to another study ovulation is characterized by a decreased blood flow of the follicular wall in the last four hours preceding it, as well as the serration of the granulosa layer and formation of a non vascularized apex, but in our ongoing study, the ability to decrease the vascularity was not found. Very vascularized follicles are associated with higher rates of oocyte maturation and pregnant that does less vascularized follicles in the preovulatory phase. Those follicles that have septated evacuation (or prolonged) showed more vascularization and serration of the granulosa one hour before ovulation than follicles that ovulate normally, and this vascularization includes the apex of the follicle, the follicular wall portion that is not vascularized in normal ovulation. Another study reported that hemorrhagic follicles have better vascularization of the follicular wall on the days preceding ovulation than follicles destined to ovulate. Some authors also showed that anovulatory follicles grow in size at the same rate as ovulatory follicles, but the percentage of vascularization of its wall is much smaller at 35 mm. Another study characterized that the vascular wall of the follicle that results in the first ovulation of the year is much smaller on the day before ovulation than the number of vessels present in a follicle that will ovulate in the middle of the breeding season. In these cases, the use of Doppler ultrasound can help to prevent economic losses as insemination of mares in cycles that are not able of resulting in pregnancy. This review aims to gather the information found in the literature about the characteristics of follicular hemodynamic of mares taking into account moments of deviation in follicle size, ovulation, ovulation failure and follicular viability. Conclusion: The Doppler technology has the potential to provide important information about the follicular environment and thus be used in practice in search of the perfect equine reproductive management, achieving better utilization of genetic material and increasing the financial return. The use of this new tool opens a large area for several interesting studies that will contribute to the knowledge of the physiological events of the mare for that this technique can soon be effectively applied.
Keywords: Blood flow; Doppler; Follicle; Follicular wall; Mare; Ovulation.; Animalia; Equidae